Minds, Machines, and the Future of Design: Rethinking Architectural Education in the Age of AI (EAAE Annual Conference Proceedings, 2023)
The introduction of computer-aided design (CAD) programs marked a significant shift in architectural practice, with professionals transitioning from hand drawing to digital tools. This evolution sparked debates on the implications of technology for the quality and authenticity of design.